PERANAN GURU DALAM PELAKSANAAN PROGRAM KURIKULUM 2013 DI MADRASAH TSANAWIYAH HIDAYATUL MUBTADI’IN BUMIAYU MALANG - Azhar Ang Haq (VICRATINA, 2018)
Teacher has an important role for the implementation of the education. Role of teachers in the 2013 curriculum more be active, lots of ideas and discipline. Teachers must be able to create a good school atmosphere. This study discussed about the role and influence of Madrasah Tsanawiyah Hidayatul Mubtadi'in's Teachers in the impelementation of the 2013 curriculum.